HA-EGCG graft copolymer and application thereof in nuts

By using the cross-linking reaction mediated by the ascorbic acid/hydrogen peroxide redox system in HA-EGCG, the grafting rate of HA-EGCG was improved, and the problems of its antioxidant performance and nut coating effect were solved, achieving Better nut preservation and biological activity maintenance.

CN119350526AActive Publication Date: 2025-01-24ZHEJIANG FORESTRY UNIVERSITY
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411938100.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-01-24
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

In the prior art, the grafting rate of HA-EGCG is low, which affects its antioxidant properties and nut coating effect.

Method used

By using the cross-linking response to the combination of anti-hemoglobin/hydrogen peroxide oxidation system, the HA-EGCG branches are prepared to increase its branching rate to 40-90%.

Benefits of technology

It improved the antioxidant properties and nut covering effects of HA-EGCG, extended the preservation value of nuts, and maintained its biological activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350526A_ABST
    Figure CN119350526A_ABST
Patent Text Reader

Abstract

A preparation method of the HA-EGCG graft copolymer comprises the following steps: taking hyaluronic acid and EGCG as reaction substrates, and adopting an ascorbic acid / hydrogen peroxide redox system to mediate a cross-linking reaction to obtain the HA-EGCG graft copolymer. The HA-EGCG graft copolymer has excellent biological activity, the nut film covering effect is well improved, and a new thought and a new way are provided for developing nut film covering and improving the biological activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biotechnology and relates to a HA-EGCG graft copolymer and application thereof in nuts. Background Art

[0002] Epigallocatechin gallate (EGCG) is the main active ingredient of flavanols in polyphenols and the catechin with the highest content in green tea. It has multiple effects such as antioxidant, antibacterial and anti-tumor. Free radical grafting is a reaction between polyphenol hydroxyl radicals and active groups on the side chains of grafted compounds to form covalent bonds. The formation of covalent bonds involves irreversible interactions, thus forming a more stable conjugate. Compared with the enzyme method and the alkaline method, the free radical grafting method does not involve organic solvents in the reaction process and has higher safety. It is widely used in the food industry. How to improve the grafting rate of HA-EGCG is one of the problems that researchers need to solve urgently.

[0003] Hyaluronic acid (HA) is an unbranched high molecular weight glycosaminoglycan composed of N-acetylglucosamine and D-glucuronic acid disaccharide repeating units through β-(1→4) glycosidic bonds and β-(1→3) glycosidic bonds. It is widely present in the interstitial tissue cells of animals and the capsules of some bacteria. Its relative molecular mass (Mr) is generally 1×10 5 ~1×10 7 D, the molar ratio of the two monosaccharides in the molecule is 1:1. HA is one of the main components of the extracellular matrix, with good biocompatibility, biodegradability and non-immunogenicity. The molecular structure is also rich in reactive functional groups such as carboxyl and hydroxyl groups that can be further chemically modified. People have conducted relatively thorough research on the structure, properties and physiological functions of HA. The average Mr of HA currently used is generally greater than 1×10 5 D. Hyaluronic acid has been widely used in drug carriers, medical cosmetology and other fields due to its excellent biocompatibility, modifiability, and biodegradability. Summary of the invention

[0004] The invention aims to provide a HA-EGCG graft copolymer with a high grafting rate, and studies the application of the HA-EGCG graft copolymer in coated nuts.

[0005] To achieve the purpose of the invention, the present invention adopts the following technical solutions: A HA-EGCG graft copolymer having a structure shown in Formula I or Formula II:

[0006] Formula I Formula II.

[0007] Furthermore, the grafting rate of the HA-EGCG graft copolymer is 40 to 90%.

[0008] On the other hand, the present invention provides a method for preparing the HA-EGCG graft copolymer, which adopts the following technical scheme: A method for preparing a HA-EGCG graft copolymer comprises taking hyaluronic acid and EGCG as reaction substrates and adopting an ascorbic acid / hydrogen peroxide oxidation-reduction system to mediate a cross-linking reaction to obtain the HA-EGCG graft copolymer.

[0009] Specifically, a method for preparing a HA-EGCG graft copolymer comprises the following steps: (1) Dissolve hyaluronic acid in deionized water, add ascorbic acid and EGCG, mix well and let stand at room temperature; (2) Adding hydrogen peroxide solution to the reaction system and reacting under a nitrogen or helium atmosphere; (3) After the reaction is completed, the dialysis bag is used for dialysis, and the dialysis solution is changed at intervals to remove the unreacted EGCG. The solution after the dialysis is freeze-dried to obtain the graft copolymer.

[0010] Preferably, the hyaluronic acid is H-HA or L-HA or a mixture thereof, wherein H-HA is a macromolecule with Mr ≥ 100,000, L-HA is a small molecule with Mr ≤ 3000, and the mixture is 0 ≤ Mr ≤ 100,000.

[0011] Preferably, the standing time in step (1) is 10 to 20 minutes; the reaction time in step (2) is 24 to 36 hours; and in step (3), the dialysate is replaced every 6 to 8 hours to remove unreacted EGCG, and the cycle is repeated three times.

[0012] Preferably, the volume-to-mass ratio of the ionized water to hyaluronic acid is 1:5-10 ml / g, the mass ratio of hyaluronic acid to ascorbic acid is 1:0.01-0.05, and the mass molar ratio of ascorbic acid to hydrogen peroxide is 1:0.5-1 g / mol.

[0013] Preferably, the molecular weight cut-off of the dialysis is 25 to 500 Da.

[0014] Preferably, the weight ratio of EGCG to HA is selected from 1:10, 1:5, 2:5, 4:5, 1:1 or 8:5.

[0015] On the other hand, the present invention also includes the use of the HA-EGCG graft copolymer in nuts.

[0016] The nuts include but are not limited to peanuts, melon seeds, almonds, torreya grandis, hazelnuts, pine nuts, cashews, pistachios, walnuts, pecans, etc.

[0017] The HA-EGCG graft copolymer is directly coated on nuts, thereby improving the preservation value of the nuts.

[0018] The graft copolymer provided by the present invention has excellent biological activity, such as good antioxidant activity and thermal stability, and greatly expands its application space in food, daily chemicals and medicine.

[0019] The present invention studies how to enhance the antioxidant properties by increasing the grafting rate of HA-EGCG, and improve the effect of nut coating. This study provides new ideas and new ways to develop nut coating to improve biological activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the antioxidant activity analysis diagram of HA-EGCG graft copolymer; Figure 2 HA-EGCG graft copolymer 1 H-Figure; Figure 3 is the microstructure diagram of HA-EGCG graft copolymer; Figure 4 is the Fourier transform infrared spectrum analysis diagram of HA-EGCG graft copolymer; Figure 5 This is the thermal stability analysis diagram of HA-EGCG graft copolymer; Figure 6 This is the change diagram of acid value content in storage of Torreya grandis coated with HA-EGCG graft copolymer; Figure 7 This is the change of peroxide value of Torreya grandis coated with HA-EGCG graft copolymer during storage; Figure 8 This is the malondialdehyde content of Torreya grandis coated with HA-EGCG graft copolymer during storage; Fig. 9 This is the storage appearance of Torreya grandis coated with HA-EGCG graft copolymer. DETAILED DESCRIPTION

[0021] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in combination with the implementation modes and the accompanying drawings.

[0022] Unless otherwise specified, the experimental methods used in the examples are all conventional methods; the materials and reagents used, unless otherwise specified, are all reagents and materials available from commercial sources.

[0023] Example 1 The steps of the preparation method of HA-EGCG graft copolymer are as follows: (1) Dissolve 0.5 g of hyaluronic acid H-HA in 100 mL of deionized water in a beaker. After the hyaluronic acid is fully dissolved and swollen, add 0.005 g of ascorbic acid and 0.05 g of EGCG to the beaker, mix well, and let stand at room temperature for 10 min. (2) Add 1 mL of 5M H2O2 to the reaction system and start the reaction under nitrogen atmosphere for 24 to 36 hours; (3) After the reaction is completed, the unreacted EGCG is removed by dialyzing with a dialysis bag. The dialysate is changed every 6 to 8 hours, and the cycle is repeated 3 times. The HA-EGCG graft copolymer solution obtained after the dialysis is completed is freeze-dried to obtain the graft copolymer. The molecular weight cutoff of the dialysis is 25 to 500 Da, and 200 Da is selected here.

[0024] According to the method of Example 1, the amounts of hyaluronic acid and EGCG were changed to obtain Examples 2 to 6, as shown in Table 1: Table 1.

[0025] Calculate the grafting rate of HA-EGCG graft copolymer in Examples 1 to 6. Grafting rate calculation: Mix 1 mL of HA-EGCG graft copolymer solution with 1 mL of Folin phenol reagent (diluted 10 times) and incubate in the dark at 30°C for 5 minutes. Subsequently, add 2 mL of 7.5% Na2CO3 to the mixture and incubate the reaction in the dark for 1 hour. The absorbance of the solution at a wavelength of 765 nm was measured, and its value was correlated with the standard curve of EGCG, where the grafting rate of HA-EGCG was expressed as a percentage of mgHA equivalent / g (mg HHA / g), and the results are shown in Table 2.

[0026] Table 2. Grafting rate of Examples 1 to 6

[0027] Example 7 The steps of the preparation method of HA-EGCG graft copolymer are as follows: (1) Dissolve 1 g of hyaluronic acid L-HA in 100 mL of deionized water in a beaker. After the hyaluronic acid is fully dissolved and swollen, add 0.05 g of ascorbic acid and 0.1 g of EGCG to the beaker, mix well, and let stand at room temperature for 10 min. (2) Add 0.5 mL of 5M H2O2 to the reaction system and start the reaction under nitrogen atmosphere for 24 to 36 hours; (3) After the reaction is completed, the unreacted EGCG is removed by dialyzing with a dialysis bag. The dialysate is changed every 6 to 8 hours, and the cycle is repeated 3 times. The HA-EGCG graft copolymer solution obtained after the dialysis is completed is freeze-dried to obtain the graft copolymer. The molecular weight cutoff of the dialysis is 25 to 500 Da, and 25 Da is selected here.

[0028] According to the method of Example 7, the amounts of hyaluronic acid and EGCG were changed to obtain Examples 8 to 12, as shown in Table 3: Table 3.

[0029] The grafting rate of the HA-EGCG graft copolymers in Examples 7 to 12 was calculated. The grafting rate was calculated in the same manner as in Example 1, and the results are shown in Table 4.

[0030] Table 4. Grafting rate of Examples 7 to 12

[0031] Example 13 The steps of the preparation method of HA-EGCG graft copolymer are as follows: (1) Take 100 mL of deionized water to dissolve 0.8 g of a mixture of hyaluronic acid H-HA and L-HA in a beaker. After the hyaluronic acid is fully dissolved and swollen, add 0.024 g of ascorbic acid and 0.08 g of EGCG to the beaker, mix well, and let stand at room temperature for 10 min. (2) Add 0.8 mL of 5M H2O2 to the reaction system and start the reaction under nitrogen atmosphere for 24 to 36 hours; (3) After the reaction is completed, the unreacted EGCG is removed by dialyzing with a dialysis bag. The dialysate is changed every 6 to 8 hours, and the cycle is repeated 3 times. The HA-EGCG graft copolymer solution obtained after the dialysis is freeze-dried to obtain the graft copolymer. The molecular weight cutoff of the dialysis is 500 Da.

[0032] According to the method of Example 13, the amounts of hyaluronic acid and EGCG were changed to obtain Examples 14 to 18, as shown in Table 5: Table 5.

[0033] The grafting rate of the HA-EGCG graft copolymers in Examples 13 to 18 was calculated. The grafting rate was calculated in the same manner as in Example 1, and the results are shown in Table 6.

[0034] Table 6. Grafting rate of Examples 13 to 18

[0035] Analysis of stability indexes of HA-EGCG graft copolymers The HA-EGCG graft copolymer solution with the highest grafting rate in the example was taken for stability analysis.

[0036] Experimental indicator 1 Antioxidant activity analysis: 0.1 mL of HA-EGCG graft copolymer was mixed with 2.8 mL of Tris-HCl buffer (100 mM, pH 8.0) and incubated at 25°C for 10 min. Then 3 mM pyropyrol solution was added, preheated in a 25°C water bath, mixed and reacted, and the absorbance at 325 nm was measured by a spectrophotometer. The results are shown in Figure 1 .O 2•− The removal capacity was calculated as O 2•− Clearance rate % = (1-sample absorbance value / blank absorbance value) × 100%.

[0037] Experimental indicator 2 Nuclear magnetic resonance analysis: Weigh 50 mg of HA-EGCG graft copolymer freeze-dried powder, dissolve it in 0.5 mL of heavy water and freeze-dry it. Then dissolve the freeze-dried powder in 0.5 mL of heavy water and continue freeze-drying. Repeat the above process to fully exchange active hydrogen. Then dissolve the sample in 0.5 mL of heavy water and place it in a 600 MHz nuclear magnetic resonance instrument at room temperature 25 ° C. 1 One-dimensional spectrum of HNMR spectrum, the results are shown in Figure 2 .

[0038] Experimental indicator 3 10 mg of HA-EGCG graft copolymer freeze-dried powder was placed on a sample grid coated with 200 mesh copper for 2 minutes, then stained with 2% phosphotungstic acid for 3 minutes, and the excess staining solution was absorbed with filter paper. The dried sample was used for TEM observation. The surface morphology of hyaluronic acid and its conjugates was observed by scanning electron microscopy (SEM). The prepared sample was fixed on a 1*1 mm single-sided polished silicon wafer, sputtered with gold, freeze-dried, and observed under a scanning electron microscope. The results are shown in Figure 3 .

[0039] Experimental indicator 4 Fourier transform infrared spectroscopy analysis: 2 mg of HA-EGCG graft copolymer freeze-dried powder was mixed with dry KBr (at a ratio of 1:100), and then pressed into 1 mm compressed particles (5-8 tons per square centimeter) using a hydraulic press to obtain a transparent film. The prepared tablets were placed in a test tube and subjected to Fourier transform infrared spectroscopy analysis. The results are shown in Figure 4 .

[0040] Experimental indicator 5 Thermal stability analysis: 2.5 mg of HA-EGCG graft copolymer freeze-dried powder was placed in a thermogravimetric furnace. Under the conditions of nitrogen flow rate of 20 mL / min and heating rate of 10°C / min, the TGA curve of the sample in the range of 50-800°C was obtained using a thermogravimetric analyzer. The results are shown in Figure 5 .

[0041] Application of HA-EGCG graft copolymer Implementation 1 Film coating process: take mature and peeled Torreya grandis, fully coat its surface with copolymer solution, and then dry it to complete the film coating.

[0042] Testing of quality indicators of coated Torreya grandis.

[0043] Application indicator 1: Acid value content. Weigh 0.5 g (accurate to 0.001 g) of the prepared sample, place it in a 250 mL iodine volumetric flask, add 7.5 mL of chloroform-glacial acetic acid solution, and gently shake the sample until it is completely dissolved. Accurately add 0.25 mL of saturated potassium iodide solution, plug the bottle cap tightly, and gently shake for 0.5 min. Place in a dark place for 3 min. Take out and add 25 mL of water, shake well and immediately titrate the solution with standard sodium thiosulfate; titrate the precipitated iodine, and when it titrates to light yellow, add 1 mL of starch indicator, continue titrating and shake vigorously until the blue color of the solution disappears as the end point. Perform a blank test at the same time. The results are as follows Figure 6 As shown, compared with the uncoated group, after three months of placement, the acid value of the coated group was 0.26367 mg / g, and the acid value of the uncoated group was 0.40392 mg / g.

[0044] Application indicator 2: Peroxide value. The measurement is carried out in accordance with GB 5009.227-2023: Weigh 2g~3g (accurate to 0.001g) of the prepared sample, place it in a 250mL iodine volumetric flask, add 30mL of chloroform-glacial acetic acid solution, and gently shake the sample until it is completely dissolved. Accurately add 1.00mL of saturated potassium iodide solution, plug the bottle cap tightly, and gently shake for 0.5min, and place in a dark place for 3min. Take out and add 100mL of water. After shaking well, immediately titrate the precipitated iodine with a standard sodium thiosulfate titration solution. When it is titrated to light yellow, add 1mL of starch indicator, continue titrating and shake vigorously until the blue color of the solution disappears as the end point. Perform a blank test at the same time. The volume V of the standard sodium thiosulfate titration solution consumed in the blank test. As Figure 7 As shown, compared with the uncoated group, after three months of placement, the peroxide value of the coated group was 0.022842 g / 100g, and the peroxide value of the uncoated group was 0.073602 g / 100g.

[0045] Application indicator 3: Malondialdehyde content. The measurement is determined in accordance with GB 5009.181-201. Weigh 5 g of the sample and place it in a 100 ml stoppered conical flask, accurately add 50 mL of trichloroacetic acid mixture, shake well, seal with a stopper, place on a constant temperature oscillator and shake at 50°C for 30 min, take out, cool to room temperature, filter with a double-layer quantitative slow filter paper, discard the initial filtrate, and keep the subsequent filtrate for later use. Accurately transfer 5 mL of the filtrate and the standard series solution into 25 mL stoppered colorimetric tubes, take another 5 mL of trichloroacetic acid mixture as the sample blank, add 5 mL of thiobarbituric acid (TBA) aqueous solution, stopper and mix well, place in a 90°C water bath to react for 30 min, take out and cool to room temperature. Use the sample blank to adjust the zero point, measure the absorbance of the sample solution and the standard series solution at 532 nm, and draw a standard curve with the mass concentration of the standard series solution as the horizontal axis and the absorbance value as the vertical axis. Figure 8 As shown, compared with the uncoated group, the malondialdehyde content in the coated group was 762.40 mg / kg after three months of placement, and the malondialdehyde content in the uncoated group was 1136.87 mg / kg.

[0046] The coated Torreya grandis has the advantage of maintaining quality during storage. The surface of the processed Torreya grandis is easily oxidized due to exposure to the air, and the texture becomes soft. The surface of the coated Torreya grandis can effectively maintain its quality due to the isolation of HA-EGCG graft copolymer. At the same time, the strong antioxidant property of EGCG can maintain the normal color of Torreya grandis. Fig. 9 As shown, the quality of coated Torreya grandis was maintained after 90 days of storage compared with untreated Torreya grandis.

[0047] Similarly, other nuts such as peanuts, melon seeds, almonds, Chinese torreya, hazelnuts, pine nuts, cashews, pistachios, walnuts, and pecans can also achieve the same effect as Chinese torreya by coating them with the copolymer solution of the present invention.

[0048] These results indicate that the biological activity of Torreya grandis is well maintained after coating, which has great potential and application value for the preservation of Torreya grandis and other nuts.

Claims

1. A HA-EGCG graft copolymer, characterized in that The HA-EGCG graft copolymer has a structure shown in Formula I or Formula II: Formula I Formula II.

2. The HA-EGCG graft copolymer according to claim 1, characterized in that The grafting rate of the HA-EGCG graft copolymer is 40 to 90%.

3. A method for preparing a HA-EGCG graft copolymer as claimed in claim 1 or 2, characterized in that, The method comprises taking hyaluronic acid and EGCG as reaction substrates and adopting ascorbic acid / hydrogen peroxide oxidation-reduction system to mediate cross-linking reaction to obtain HA-EGCG graft copolymer.

4. The method for preparing a HA-EGCG graft copolymer according to claim 3, characterized in that: The hyaluronic acid is H-HA or L-HA or a mixture thereof, wherein H-HA is a macromolecule with Mr≥100,000, L-HA is a small molecule with Mr≤3000, and the mixture is 0≤Mr≤100,000.

5. The method for preparing a HA-EGCG graft copolymer according to claim 3, characterized in that: The steps include: (1) Dissolve hyaluronic acid in deionized water, add ascorbic acid and EGCG, mix well and let stand at room temperature; (2) Adding hydrogen peroxide solution to the reaction system and reacting under a nitrogen or helium atmosphere; (3) After the reaction is completed, dialyze using a dialysis bag, change the dialysis solution at intervals to remove unreacted EGCG, and freeze-dry the solution after dialysis.

6. The method for preparing a HA-EGCG graft copolymer according to claim 5, characterized in that: The volume-to-mass ratio of the ionized water to the hyaluronic acid is 1:5-10 l / g, the mass ratio of the hyaluronic acid to the ascorbic acid is 1:0.01-0.05, and the mass molar ratio of the ascorbic acid to the hydrogen peroxide is 1:0.5-1 g / mol.

7. The method for preparing a HA-EGCG graft copolymer according to claim 6, characterized in that: The molecular weight cut-off of the dialysis is 25 to 500 Da.

8. The method for preparing a HA-EGCG graft copolymer according to claim 5, characterized in that: The weight ratio of EGCG to HA is selected from 1:10, 1:5, 2:5, 4:5, 1:1 or 8:

5.

9. Use of the HA-EGCG graft copolymer according to claim 1 in nuts.

10. The use according to claim 9, characterized in that: The nuts include but are not limited to peanuts, melon seeds, almonds, torreya grandis, hazelnuts, pine nuts, cashews, pistachios, walnuts or pecans.

Citation Information

Patent Citations

  • Synthesis method of inulin-catechin graft copolymer with strong antioxidation activity

    CN104877047A

  • Chlorogenic acid grafted modified starch, degradable preservative film and preparation method thereof

    CN110885380A

  • Conjugates and nanoparticles of hyaluronic acid and epigallocatechin-3-O-gallate and uses thereof

    CN113365613A

  • Modified polyphenol carrier material, targeted nano delivery system, preparation method and application

    CN115702937A

  • Application of polyphenol polymer in preparation of anti-tumor drugs for starvation therapy

    CN115869336A